Sleep, stress and compensatory behaviors in Australian nurses and midwives Sueño, estrés y comportamientos compensatorios por enfermeras y parteras australianas Sono, estresse e comportamentos compensatórios por enfermeiras e parteiras australianas - Jillian Dorrian; Jessica Paterson; Drew Dawson; Jan Pincombe; Carol Grech; Ann E Rogers (Universidade de São Paulo, 2011)
OBJECTIVE: To describe sleep, stress and compensatory behaviors in nurses and midwives. METHODS: The study included 41 midwives and 21 nurses working in Australian hospitals between 2005 and 2009. Participation was voluntary. All participants recorded on a daily basis their work and sleep hours, levels of stress and exhaustion, caffeine intake and use of sleep aids for a month (1,736 days, 1,002 work shifts). RESULTS: Participants reported moderate to high levels of stress and exhaustion on 20-40% of work days; experienced sleep disruption on more than 50% of work days; struggled to remain awake on 27% of work days; and suffered extreme drowsiness or experienced a near accident while travelling home on 9% of workdays. Age, perceived sleep duration and work hours were significant predictors of caffeine intake. About 60% of participants reported using sleep aids (about 20% reported taking prescription medications and 44% of nurses and 9% of midwives reported alcohol use as a sleep aid at least once during the study). Stress and workdays were significant predictors of sedative use. Overall, 22% reported being indifferent or mildly dissatisfied with their job. CONCLUSIONS: Sleep problems, high levels of stress and exhaustion and low job satisfaction are prevalent among nurses and midwives. The use of alcohol and sleeping pills as sleep aids, and the use of caffeine to help maintain alertness is also common. Nurses and midwives may use caffeine to compensate for reduced sleep, especially on workdays, and sleeping pills to cope with their daily work-related stress. OBJETIVO: Describir sueño, estrés y comportamientos compensatorios en enfermeras y parteras. MÉTODOS: El estudio incluyó 41 enfermeras 21 parteras en hospitales australianos de 2005 a 2009. La participación fue voluntaria. Los participantes registraron diariamente las horas de trabajo, sueño, estrés y niveles de agotamiento, cafeína y uso de ayuda para dormir durante un mes (1.736 días, 1.002 turnos). RESULTADOS: Los participantes relataron de moderados a elevados niveles de estrés y de agotamiento en 20%-40% de los días de trabajo; experimentaron disturbios del sueño en más de 50% de los días de trabajo; relataron esfuerzo para permanecer despierto en 27% de los días de trabajo; y sofrieron somnolencia extrema o accidente cerca de casa en 9% de los días de trabajo. Edad, duración del sueño percibido y jornadas fueron predictores significativos de la ingestión de cafeína. Aproximadamente 60% de los participantes relataron utilizar la ayuda para dormir: cerca de 20% usaron de medicación prescripta y 44% de las enfermeras y 9% de las parteras consumirán alcohol como auxilio para dormir al menos una vez durante el estudio. Estrés y días de trabajo fueron predictores significativos del uso de sedativos. En general, 22% relataron ser indiferente, o ligeramente insatisfecho con su trabajo. CONCLUSIONES: Problemas en el sueño, estrés y agotamiento elevados y disminución en la satisfacción en el trabajo son prevalecientes. Uso de alcohol y de medicamentos para dormir, y consumo de cafeína para mantenerse alerta también es común. Enfermeras y parteras pueden usar la cafeína para compensar la reducción del sueño, especialmente en días de trabajo, y usar somníferos para compensar el estrés diario. OBJETIVO: Descrever sono, estresse e comportamentos compensatórios em enfermeiras e parteiras. MÉTODOS: O estudo incluiu 41 enfermeiras 21 parteiras em hospitais australianos de 2005 a 2009. A participação foi voluntária. Os participantes registraram diariamente as horas de trabalho, sono, stress e níveis de exaustão, cafeína e uso de ajuda para dormir durante um mês (1.736 dias, 1.002 turnos). RESULTADOS: Os participantes relataram de moderados a elevados níveis de stress e de exaustão em 20%-40% dos dias de trabalho; experimentaram distúrbios do sono em mais de 50% dos dias de trabalho; relataram esforço para permanecer acordado em 27% dos dias de trabalho; e sofreram sonolência extrema ou acidente perto de casa em 9% dos dias de trabalho. Idade, duração do sono percebida e jornadas foram preditores significativos da ingestão de cafeína. Aproximadamente 60% dos participantes relataram utilizar a ajuda para dormir: cerca de 20% relataram uso de medicação prescrita e 44% das enfermeiras e 9% das parteiras consumiam álcool como auxílio para dormir pelo menos uma vez durante o estudo. Estresse e dias de trabalho foram preditores significativos do uso de sedativos. Em geral, 22% relataram ser indiferente, ou ligeiramente insatisfeito com seu trabalho. CONCLUSÕES: Problemas no sono, estresse e exaustão elevados e diminuição na satisfação no trabalho são prevalentes. São comuns o uso de álcool e de medicamentos para dormir, e consumo de cafeína para se manter alerta. Enfermeiras e parteiras parecem usar a cafeína para compensar a redução do sono, especialmente em dias de trabalho, e usar soníferos para compensar o estresse diário.